Intraoral epithelioid hemangioendothelioma: An intermediate vascular tumor- A case report - Bhari Sharanesha Manjunatha; Gopal Siva Kumar; Raghunath Vandana (Wolters Kluwer Medknow Publications, 2009)
Vascular neoplasms, other than benign are characterized as intermediate or malignant. They are often enshrouded in controversy, because the same neoplasm could show variability in biologic behavior that may not be correlated with microscopic features. The intermediate grade vascular neoplasm is named as epithelioid hemangioendothelioma (EHE). Epithelioid hemangioendothelioma of the oral cavity has been infrequently reported. To the best of our knowledge, the review of the English litera-ture revealed a total of 30 cases of intraoral EHE reported till today. We report such a rare case in a 20 year old male, presented with a growth in lower anterior lingual gingiva since five months before the diagnosis with a history of similar swelling, twice in the same area. The differential diagnosis and brief review of literature is also discussed in the current article.